Tahlil Su’ubāt Ta’allum al Lughah al Arabiyyah Li Thullāb Fashl al Tsāni al Madrasah al Tsānawiyah al Salafiyah al Syāfi’iyah Seblak Jombang - Nur Ahmad, Muntabakun; Abdul Qodir (Program Studi Pendidikan Bahasa Arab, 2024)
This study aims to determine the learning difficulties Arabic language experienced by grade 2 students of Madrasah Tsanawiyah Syalafiyah Syafi'iyah Seblak Jombang in learning Arabic. The analysis was conducted by looking at the approaches and methods used by the teacher. This research uses descriptive qualitative methods where data is collected through observation, interviews, and documentation. The results showed that the difficulties experienced by students in terms of the approach used by the teacher is a structural approach. where the teacher demands understanding of formulas and terms while the level of understanding of students varies. The causes of these difficulties include lack of motivation, limited vocabulary, difficulty in understanding Arabic writing, and inadequate learning facilities. In addition, the teacher's limited ability to create an interesting learning environment and students' lack of practice also contribute to learning difficulties. Another difficulty is in terms of memorization methods used by teachers, due to students' lack of memory. To overcome these problems, a solution is needed in the form of using learning methods and approaches that are in accordance with the characteristics of students so that the learning process becomes more effective and provides additional support for students who have difficulty in learning Arabic. This is expected to improve the quality of Arabic language learning in the Madrasah.